Chlorophytum borivilianum Polysaccharide Fraction Provokes the Immune Function and Disease Resistance of Labeo rohita against Aeromonas hydrophila. (15th November 2015) - Giri, Sib Sankar; Sen, Shib Sankar; Chi, Cheng; Kim, Hyoun Joong; Yun, Saekil; Park, Se Chang; Sukumaran, V.
Abstract : The present study aimed to investigate the effects of Chlorophytum borivilianum polysaccharide (CBP), as a dietary supplement administered at varying concentrations with feed (basal diet), on various cytokine-related responses in Labeo rohita fingerlings. Immune parameters and immune-related gene expressions were measured at 3rd, 4th, and 5th week after feeding. The results revealed that dietary administration of CBP at 0.2% and 0.4% for 4 weeks significantly upregulated serum lysozyme and phagocytic activity. Complement C3 and respiratory burst activity (RBA) were significantly higher after 4 weeks of CBP feeding. The immune related genes IL-8, IL-1 β, TNF- α, and iNOS were downregulated (P < 0.05 ) in groups with 0.2% and 0.4% CBP supplemented diets at week 4. Expression of anti-inflammatory cytokines ( IL-10 and TGF- β ) was also downregulated (P < 0.5 ) after 4 weeks of feeding with 0.2% to 0.8% CBP. However, five weeks of CBP administration had no significant effect on immune gene expression, except TNF- α and IL-8 . Fish fed with 0.4% CBP for 4 weeks showed maximum resistance against Aeromonas hydrophila (73.3% survival) compared to control. From these results, we recommend that CBP administration at 0.4% for 4 weeks could effectively improve immune response and disease resistance in L. rohita .